A pressure-based algorithm for internal compressible turbulent flows through a geometrical singularity. (1st February 2019) - Nouri-Borujerdi, Ali; Shafiei Ghazani, Ardalan
Abstract: Compressible turbulent flow through the abrupt enlargement in pipes is studied numerically by means of Advection Upstream Splitting Method (AUSM+-up). In low Mach numbers, a pressure correction equation of elliptic type is derived. This equation is compatible with the nature of governing equations and retrieves hyperbolic characteristic at higher Mach numbers. It is shown that the proposed numerical algorithm is computationally more efficient than the preconditioned density-based methods. The flow parameters such as reattachment length, pressure loss coefficient and wall shear stress are predicted. It is found that the loss coefficient of the compressible flow rises drastically with increasing Reynolds number while it is constant for incompressible flows. Furthermore, the total-pressure ratio drops with increasing Reynolds number and expansion ratio where it approaches an asymptotic curve. In compressible flow, the pressure is minimum and constant after the enlargement section up to the axial position of the recirculation center.